2001
DOI: 10.1038/sj.bjp.0704217
|View full text |Cite
|
Sign up to set email alerts
|

A novel tachykinin NK2 receptor antagonist prevents motility‐stimulating effects of neurokinin A in small intestine

Abstract: 1 MEN 11420 (nepadutant) is a potent, selective and competitive antagonist of tachykinin NK2 receptors. 2 The objective of the present study was to assess the capability of the drug to antagonize the stimulatory eects of neurokinin A (NKA) on gastrointestinal motility, as well as to change the fasting migrating motor complex (MMC). 3 Thirty-four male volunteers were randomized to treatment with either placebo or MEN 11420 in a double-blinded manner. Eects of MEN 11420 (8 mg intravenously) were evaluated as cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 34 publications
(41 reference statements)
3
45
0
Order By: Relevance
“…Jaafari et al (22) reported that TACR2 alpha mRNA encoding NK 2 -R was predominantly expressed in the normal human colon. Furthermore, Lordal et al (23,24) demonstrated that intravenous infusion of NKA in healthy volunteers could induce marked contraction of the small intestine and was inhibited by the NK 2 -Rselective antagonist nepadutant. These results strongly support our findings and suggest that our in vitro findings could translate into an in vivo clinical setting.…”
Section: Vehicle Atropinementioning
confidence: 99%
“…Jaafari et al (22) reported that TACR2 alpha mRNA encoding NK 2 -R was predominantly expressed in the normal human colon. Furthermore, Lordal et al (23,24) demonstrated that intravenous infusion of NKA in healthy volunteers could induce marked contraction of the small intestine and was inhibited by the NK 2 -Rselective antagonist nepadutant. These results strongly support our findings and suggest that our in vitro findings could translate into an in vivo clinical setting.…”
Section: Vehicle Atropinementioning
confidence: 99%
“…Clinical data is currently deficient. However, in one study of healthy volunteers using the selective NK2 antagonist nepadutant (MEN11420), IBS-like symptoms triggered by the infusion of neurokinin A were reduced [108] . Saredutant (SR48968), another NK2 antag onist, is also being developed for the treatment of IBS, but clinical results are not yet available.…”
Section: Neurokinin Antagonistsmentioning
confidence: 99%
“…NK1 receptors seem to be primarily involved in the physiological control of motility, whereas NK2 receptors seem to exert a prominent role in inflammation and control of motility in pathological conditions (Lecci et al, 1994;Holzer and Holzer-Petsche, 1997;Lecci et al, 1997;Maggi, 1997). For example, NK2 receptor antagonists can exert prominent effects on abdominal cramping or the number of intestinal contractions evoked by rectal distension (Julia et al, 1994;Santicioli et al, 1997;Toulouse et al, 2000;Lordal et al, 2001;Patacchini and Maggi, 2001). …”
mentioning
confidence: 99%